HABITUATION OF MANNERS AND MORALS THROUGH TPQ NURURROHMAH: IMPLEMENTATION OF THE INTEGRATED PKM PROGRAM IN SELO VILLAGE - dwijayanti, ita; Agustina, Sari (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
The formation of character based on adab and akhlak is one of the primary objectives in Islamic education. Taman Pendidikan Al-Qur'an (TPQ) plays a crucial role in instilling these values in children from an early age. This study examines the role of TPQ in shaping children's character through teaching manners and morals. This study uses a descriptive qualitative approach to deeply understand the process of habituation of manners and morals at TPQ Nururrohmah, Selo Village. Data collection techniques used in this study are participatory observation, interviews, and documentation.The findings reveal that TPQ Nururrohmah has successfully implemented a character-building program that focuses on instilling adab and akhlak values in children. The program is designed to promote good behavior, discipline, and moral values in children, which are essential for their personal and social development. The study concludes that TPQ Nururrohmah has a significant impact on the formation of character in children, and its approach can be replicated in other Islamic educational institutiochns. The existence of a community service program at TPQ Nururrohmah, which consists of 11 people, makes it more conducive and more organized, because the ratio of teachers to students is 1 teacher to approximately 6 students. With the existence of a community service program at TPQ Nururrohmah, learning becomes more conducive, marked by a structured learning environment and harmonious interactions between teachers and students.